2023
DOI: 10.1017/s0954102023000020
|View full text |Cite
|
Sign up to set email alerts
|

Researchers on ice? How the COVID-19 pandemic has impacted Antarctic researchers

Abstract: The COVID-19 pandemic and pandemic-related measures have impacted the lives and work-related activities of Antarctic researchers. To explore these impacts, we designed, piloted and disseminated an online survey in English, Russian, Spanish and Chinese in late 2020 and early 2021. The survey explored how the pandemic affected the productivity of Antarctic researchers, their career prospects and their mental wellbeing. Findings exposed patterns of inequities. For instance, of the 406 unique responses to the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…This signals a potential loss from academia of talented individuals within these groups. The disproportionate impacts of the pandemic identified through our survey align with other studies, such as ECRs in Antarctic research (Liggett et al, 2023) and disabled researchers in science, technology, engineering, and mathematics (Douglas et al, 2022). We postulate that disabled researchers encounter various barriers that could exacerbate longer-term challenges posed by the pandemic.…”
Section: Longer-term Impacts Of the Pandemic On Volcanology Researche...supporting
confidence: 75%
See 1 more Smart Citation
“…This signals a potential loss from academia of talented individuals within these groups. The disproportionate impacts of the pandemic identified through our survey align with other studies, such as ECRs in Antarctic research (Liggett et al, 2023) and disabled researchers in science, technology, engineering, and mathematics (Douglas et al, 2022). We postulate that disabled researchers encounter various barriers that could exacerbate longer-term challenges posed by the pandemic.…”
Section: Longer-term Impacts Of the Pandemic On Volcanology Researche...supporting
confidence: 75%
“…The pandemic has brought to light significant disparities in various research disciplines and among scientists of different demographics or backgrounds. The pandemic disproportionately affected women researchers (Cui et al, 2022;Myers et al, 2020;Korbel and Stegle, 2020;Squazzoni et al, 2020;Johnson et al, 2021;Liggett et al, 2023), under-represented racial minorities (Staniscuaski et al, 2021;Douglas et al, 2022), researchers with childcare responsibilities (Myers et al, 2020;Johnson et al, 2021;Krukowski et al, 2021), early career researchers (Fosci et al, 2020;Jackman et al, 2022;Liggett et al, 2023), and researchers with physical or mental health disabilities (Armitage and Nellums, 2020;Sarju, 2021;Douglas et al, 2022). The pronounced disruption experienced by these groups raises concerns as the impacts could potentially be long-lasting and the extent of such impacts remains uncertain (Johnson et al, 2021;Gao et al, 2021), with the possibility of exacerbating existing inequalities within the research community (Heo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Caring responsibilities can thus significantly impede career advancement, especially in sectors in which international mobility either is required or is linked to networking and prestige. Barriers for caregivers have been exacerbated by the COVID-19 pandemic, including in Antarctic research (Liggett & Herbert 2021).…”
Section: Intersectionality and Scientific Internationalismmentioning
confidence: 99%
“…In their study of Australian Antarctic research, Nash et al (2019) identified a range of challenges that women Antarctic researchers face, from physical barriers, unpaid work and gender bias to lack of opportunities and sexual harassment (see also Nash & Nielsen 2020, Barros-Delben et al 2020. These challenges are widespread, manifesting both in Antarctic fieldwork and in other Antarctic work settings across the world, as has been underscored in numerous publications (see Bell & Koenig 2017, Starkweather et al 2018, Nash & Nielsen 2020 (Liggett & Herbert 2021).…”
mentioning
confidence: 99%